Snakebite treatment in Tanzania: identifying gaps in community practices and hospital resources - Margono, Felicia; Outwater, Anne H.; Wilson, Michael; Howell, Kim M.; Bärnighausen, Till (International journal of environmental research and public health, 2022)
Snakebite envenoming causes more than 140,000 deaths annually and at least triple this number of disabilities. The World Health Organization classified snakebite as a Neglected Tropical Disease in 2017 and developed a strategy to halve death and disability from snakebite by 2030. To achieve this goal, snakebite victims need to receive safe and effective treatment. This descriptive, cross-sectional study surveyed student health professionals (N = 312) in Dar es Salaam, Tanzania, and was designed to identify major gaps in community practices and hospital resources for snakebite treatment. Participants reported using traditional community practices (44%, 95% confidence interval (CI) = 39-50%), allopathic practices (7%, 95% CI = 5-11%), or a combination of both (49%, 95% CI = 43-54%) to treat snakebite. Harmful practices included tight arterial tourniquets (46%, 95% CI = 41-52%) and wound incisions (15%, 95% CI = 11-19%). Many participants (35%, 95% CI = 29-40%) also turned to traditional healers. Students who treated snakebite injuries within the last 5 years (N = 69) also reported their general experiences with snakebite in hospitals. Hospitals often lacked essential resources to treat snakebite victims, and 44% (95% CI = 30-59%) of snakebite victims arrived at a hospital only three or more hours after the bite. A significant percentage of snakebite victims experienced lasting damage (32%, 95% CI = 20-47%) or death (14%, 95% CI = 7-25%). Snakebite outcomes could likely be improved if hospitals were universally and consistently equipped with the essential resources to treat snakebite victims, such as antivenoms. Educational interventions aimed at communities should focus on discouraging tourniquet use and tampering with the wound. Collaboration between the allopathic and traditional health system could further boost snakebite outcomes because traditional healers are often the first health workers to see snakebite victims.